THE ROLE OF THE INTERNATIONAL WORLD IN THE CONFLICT BETWEEN PALESTINE AND ISRAEL AS A PREVENTION OF HUMANITARIAN CRIMES FROM AN INTERNATIONAL LAW PERSPECTIVE - Lasia, Qorry Ulfah (NOMOI Law Review, 2023)
This research is interesting to discuss because the conflict between Israel and Palestine has never ended, while there have been so many victims. International countries also did not react because they were deemed unable to intervene directly due to limited legal sovereignty in Israel's territorial area so they were unable to intervene directly. The type of research used is in the form of normative juridical research sourced from secondary data through data processing from primary legal materials, secondary legal materials and tertiary law. Based on the results of this research, it is known that countries can intervene through UN organizational institutions by becoming a forum for socializing conflict countries as seen from the territorial divisions that the UN has carried out in order to achieve peace between the Israeli-Palestinian conflict and its nature is only as a mediator. Meanwhile, regarding countries that violate humanitarian law, it is regulated in the 1949 Geneva Convention which regulates war victims. It contains objects and subjects of war which may or may not become victims of war. If a country in conflict violates mutually agreed provisions, it can be given full responsibility for the entity of that country if it does not comply with international law that has been agreed because the convention is universally binding for countries in conflict and countries that are not in a state of conflict.